A fibrinogen-related protein, LvFREP2, from Litopenaeus vannamei facilitates the clearance of Vibrio harveyi. Issue 78 (July 2018) - Tian, Yushun; Chen, Ting; Luo, Peng; Huang, Wen; Huo, Da; Yun, Long; Hu, Chaoqun; Cheng, Chuhang
Abstract: Fibrinogen-related proteins (FREPs) play a crucial role in invertebrate immune response. In this study, we acquired a novel fibrinogen-related protein gene in Litopenaeus vannamei coding for one kind of fibrinogen-related protein, designated as Lv FREP2. The complete cDNA sequence of Lv FREP2 was 1903 bp long, containing an open reading frame of 1479 bp coding for Lv FREP2. The Lv FREP2 protein contained a putative signal peptide and a fibrinogen-related protein domain. qRT-PCRs indicated that Lv FREP2 mRNA ubiquitously distributed in all examined tissues, and it was up-regulated in gills after V. harveyi and LPS challenges. The recombinant Lv FREP2 agglutinated Gram-positive ( Staphylococcus aureus ) and Gram-negative bacteria ( Vibrio alginolyticus, V. cholerae, V. vulnificus, V. parahaemolyticus, V. harveyi, Pseudomonas aeruginosa, P. fluorescens ) in a calcium-dependent manner. Lv FREP2 also facilitated the clearance of Vibrio harveyi in vivo . Therefore, our results suggested that lv FREP2 may have important roles in the anti-bacterial immunity of L. vannamei.